Revolutionary landscapes: the PCTP/MRPP mural paintings in the Lisbon Metropolitan Area - Carmo,André (2011)
This article investigates the mural paintings made by the PCTP/MRPP in the Lisbon Metropolitan area, in the aftermath of the 1974 Portuguese revolution. Drawing on Erwin Panofsky's iconographic method of interpretation, murals are explored from an integrated landscape approach that combines two perspectives: landscapes as representations and landscapes as material artifacts. Findings suggest that the PCTP/MRPP mural paintings translated the visual ideology of social transformation and revolution underlying its politics. Furthermore, they also crystallized performative revolutionary landscapes, in the sense that they materialized acts of collective artistic citizenship, in which the social space of mural production played a fundamental role